The Changing Perception of Death and Burial: A Look at the Nigerian Obituaries - Ogbuagu, Stella C. (Anthropologica, 2022)
Lavish and expensive funerals, long delays before burial and elaborate death notices in national and local newspapers reflect a change in attitudes towards death and burial in Southern Nigeria. The author examines certain features which once characterized funerary practice among the peoples of Southern Nigeria in order to demonstrate the changes which have occurred as a result of economic affluence, technological innovation and foreign religions (Christianity). These changes are documented by means of a content analysis of Nigerian newspapers and data based on 179 personal interviews.